ANALISIS TINDAK PIDANA PERJUDIAN: STUDI KASUS BERDASARKAN BAP KELOMPOK - Samara, Finsensius; Betekeneng, Kristina; Angela Manafe, Stefany Berlin; Rizky, Tengku; Fikram Tapoin , Fransisko (Gapenas Publisher, 2024)
This study analyzes gambling crimes with a focus on the Dato Hasan Sarabiti case, which is regulated in Article 303 of the Criminal Code. The study includes an evaluation of the investigation, investigation, indictment preparation, and trial process. The results of the analysis showed that the elements of the gambling crime, such as betting activities, gambling tools, and the intentionality of the perpetrator, had been met. The investigation process is carried out in accordance with Article 184 of the Criminal Code, by prioritizing valid evidence such as witness statements, suspect confessions, and evidence. In addition, juridical and non-juridical considerations, including social and economic impacts, also affect the judge's decision in making a decision. The study highlights the importance of a holistic approach in eradicating gambling crimes. This approach includes strict law enforcement, public education about the dangers of gambling, and strengthening regulations to prevent the spread of negative gambling impacts. With these measures, it is hoped that a safer social environment can be created, free from the influence of gambling.